a-11/33=-2

Simple and best practice solution for a-11/33=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a-11/33=-2 equation:



a-11/33=-2
We move all terms to the left:
a-11/33-(-2)=0
We add all the numbers together, and all the variables
a+2-11/33=0
We multiply all the terms by the denominator
a*33-11+2*33=0
We add all the numbers together, and all the variables
a*33+55=0
Wy multiply elements
33a+55=0
We move all terms containing a to the left, all other terms to the right
33a=-55
a=-55/33
a=-1+2/3

See similar equations:

| 20/33=90/x | | 16a2+6=7 | | (x^2-4x-12)(2x+10)=0 | | 4(x-19)=96 | | 8g=8g+9 | | 12-3x=4x-5x | | 7z^2-38+15=0 | | 5x−2(x−2)=−11 | | 8=-8w+6(w-2) | | 16+2x-6=4x+5-2x | | 4y+34+4y-2=64 | | 8÷t=242 | | 5f+14=f-6* | | t-8=242 | | x=3.8x | | -4.4z=44 | | 3w+11=w+27 | | x+1=−5 | | 1/5(2x=10)+4x=-3(1/5x+4) | | n=0.5+35 | | 18y+11=14y+15 | | 4x+26x+12+50=180 | | d=3-12 | | 4x+(-60)=0 | | 2x+2x=24x | | 7(-3x+14)=-49 | | b+3=2b-44 | | 47.40=3.95g | | -60x+4=0 | | 12-1/6d=18 | | 7+x/2=2 | | 1/2y-4=11 |

Equations solver categories